Upaya Guru PAI dalam Menanggulangi Kenakalan Siswa di MA Bahrul Ulum Tambakberas Jombang - Isnan Aziz; Waslah Waslah; Dian Kusuma Wardani (JoEMS (Journal of Education and Management Studies), 2022)
The main problem of this thesis is about the delinquency of students at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang, aiming to find out the efforts of teachers in overcoming student delinquency at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. The research focus in this thesis is 1) How are the efforts of PAI teachers in dealing with student delinquency at Madrasah Aliyah Bahrul Ulum, 2) how are the factors that support and hinder the efforts of Pai teachers in overcoming delinquency of students at Madrasah Aliyah Bahrul Ulum. This research is a qualitative field research that examines the Efforts of Islamic Religious Education Teachers in Overcoming Student Delinquency at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. This type of research is qualitative research and uses a descriptive analysis approach. The results of this study are that the results of observations, fields, interviews related to the topic of determination, with reference to, the forms of delinquency of students in Madrasah Aliyah Bahrul Ulum Like; truant, likes to go to school late, does not wear the appropriate uniform for the day, smokes, fights, is busy in class, cheats on exams, does not pay attention to studying, it is difficult to regulate the efforts of PAI teachers in handling delinquency behavior of students at Madrasah Aliyah Bahrul Ullum there are efforts preventive, curative, repressive efforts. The main problem of this thesis is about the delinquency of students at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang, aiming to find out the efforts of teachers in overcoming student delinquency at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. The research focus in this thesis is 1) How are the efforts of PAI teachers in dealing with student delinquency at Madrasah Aliyah Bahrul Ulum, 2) how are the factors that support and hinder the efforts of Pai teachers in overcoming delinquency of students at Madrasah Aliyah Bahrul Ulum. This research is a qualitative field research that examines the Efforts of Islamic Religious Education Teachers in Overcoming Student Delinquency at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang. This type of research is qualitative research and uses a descriptive analysis approach. The results of this study are that the results of observations, fields, interviews related to the topic of determination, with reference to, the forms of delinquency of students in Madrasah Aliyah Bahrul Ulum Like; truant, likes to go to school late, does not wear the appropriate uniform for the day, smokes, fights, is busy in class, cheats on exams, does not pay attention to studying, it is difficult to regulate the efforts of PAI teachers in handling delinquency behavior of students at Madrasah Aliyah Bahrul Ullum there are efforts preventive, curative, repressive efforts.